Effective Modulating Brassinosteroids Signal to Study Their Specific Regulation of Reproductive Development and Enhance Yield - Zu, Song-Hao; Jiang, Yu-Tong; Hu, Li-Qin; Zhang, Yan-Jie; Chang, Jin-Hui; Xue, Hong-Wei; Lin, Wen-Hui (Frontiers in Plant Science, 2019)
Brassinosteroid (BR) is a family of bioactive steroid hormones that play vital roles in plant growth and development. Brassinosteroid regulation of plant growth and architecture is well studied. Fewer studies have investigated BR regulation of reproductive development because it is difficult to exclude non-specific regulation and secondary responses from severe vegetative phenotypes and poor nutritional status. Furthermore, differential regulation of the BR signal in vegetative and reproductive organs is difficult. Thus, establishment of a method to modulate the BR signal only in reproductive organs or at reproductive developmental stages will be beneficial. In addition, BR application in agriculture is limited because of side-effects, such as reduction in planting density and lodging resistance, and increasing the BR signal may lead to feedback inhibition. In this study, we established a transformation system for modulation of the BR signal in reproductive and vegetative development differentially. The procedure comprises transformation with different combinations of a reproductive tissue-specific promoter, coding sequences that increase or decrease the BR signal, and different genotypic backgrounds with enhanced or reduced BR signal. The enhanced BR signal generated in transformants was targeted to reproductive organs without affecting vegetative organs. This system could be used in the study of BR-specific regulation of plant reproductive development, and also shows potential utility for optimization of seed yield.